Organizational Communication and Pensioners’ Satisfaction: A Mediation Analysis of Trust in Monopolistic Public Service - Jaya, Ida; Rozzana, Mira; Gumay, Nanda Fathiyah (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
This study investigates the complex interplay between organizational communication, trust, and satisfaction among pensioners in the context of a mandatory public service. While trust is conventionally viewed as a key driver of satisfaction, this study explores whether this holds true for monopolistic institutions such as TASPEN in Indonesia. Using a quantitative explanatory design, data were collected from 78 pensioners [asumsikan jumlah sampel] at a provincial branch and analyzed using SEM-PLS (SmartPLS 3.0). The findings revealed a robust positive impact of organizational communication on both satisfaction and trust. However, surprisingly, trust does not significantly mediate or influence pensioners' satisfaction. This "trust paradox" suggests that in mandatory services, functional communication and information accuracy are more critical than trust. These results provide a new theoretical perspective for public administration: in non-competitive service environments, satisfaction is driven primarily by informational efficiency rather than emotional confidence in the provider.